Kinetics and Mechanism of Cadmium, Copper and Lead Ion Biosorption Using Aspergillus Flavus 44-1 Live Biomass - Kok, Kean Hin (2002)
Study on the feasibility of using live biomass of Aspergil/us flavus as biosorbent to remove heavy metals, such as cadmium (Cd), copper (Cu) and lead (Pb) from solution was carried out in batch sorption isotherm experiments using 500.0 mL shake flask and 2 L stirred tank reactor. The effect of metal concentration (0 - 480.0 mg/L), biosorbent concentration (0 - 5.0 g/L), pH (pH 1.0 - pH 5.0) and tempenrture (l0.0°C - 60.0°C) were investigated in single (Cd, Cu, Pb) and multimetals (CdCu, CdPb, CuPb, CdCuPb) system. Preliminary study on the biosorption heat of metal ions (Cd2+, Cu2+, Pb2+) on Aspergillus flavus was also conducted. Microscopic study using Scanning and Transmission Electron Microscope and X-ray Energy Dispersive analysis were also performed. Results obtained from single cadmium (Cd), copper (Cu) and lead (Pb) system in the shake flask experiments revealed that biomass of Ajpergillus flavus was a potential biosorbent for the removal of Cd, Cu and Pb from solution. Optimum pH for the maximum removal of Cd, Cu and Pb was at pH 2.0, pH 5.0 and pH 4.0, respectively. Optimum temperature for the maximum removal of Cd, Cu and Pb was occurred at 30.0°C, 30.0°C and 40.0°C, respectively. Results from this study also showed that a small amount of Aspergillus flavus biosorbent, less than 0.6g, was sufficient to remove a significant large amount of metal ions, almost 23.33 mg/L (Cd2+, Cu2+, Pb2+) from 100.0 mglL solution. In the dual (CdCu, CdPb, CuPb) and tri-metals (CdCuPb) system, removal of cadmium (Cd), copper (Cu) and lead (Pb) from solution were interfered by the presence of inhibiting cations. The presence of competing ions have altered the equilibrium state and stability of solution chemistry of the system. The system would shift to another equilibrium in favour of the more influenced ion in the system. Performance of biosorption in a more controlled surrounding in enclosed contactor, such as stirred tank reactor was preferred by the industry. Maximum lead uptake (59.70 mg/g) by Aspergillus jlavus in stirred tank reactor could be achieved at pH 5.0, 30.0°C and biosorbent (Aspergillus jlavus) concentration of 2.0 g/L. Biosorption data of cadmium (Cd), copper (Cu) and lead (Pb) adsorption, in single Cd, Cu and Pb system revealed that the Langmuir, Scatchard and Freundlich models were applicable to the biosorption system. However, the applicability of these adsorption models in the dual( Cdeu, CdPb, CuPb) and trimetals (CdCuPb) system were not encouraging. Desorption with appropriate eluant (HCl, HN03, H2 S04) was able to recover the metal ion (Cd²⁺, Cu²⁺, Pb²⁺) from solution and prevent secondary pollution to our environment. The possibility of generatingthe absorb at (Aspergillus flavus) have led to the development of this promising technology.